Coping with daily hindrance and challenge stressors in the workplace: coping style effects on state negative affect - Turgut, Sarah; Michel, Alexandra; Sonntag, Karlheinz (Zeitschrift für Arbeits- und Organisationspsychologie, 2017)
This study examined daily hindrance and challenge stressors at work (rated after work) for effects on employees’ state negative affect at the beginning of the next workday. Building on the transactional stress model, the authors also examine whether general coping styles impact the relationships. Multilevel analyses show that previous-day hindrance stressors are positively related to next-day state negative affect, whereas previous-day challenge stressors are not significantly related to next-day state negative affect. The study identifies differential effects of problem-focused versus emotion-focused coping styles: High use of emotion-focused coping style increases state negative affect for both challenge and hindrance stressors; a lack of problem-focused coping style strengthens challenge stressors’ positive effect on state negative affect. The results suggest that occupational health can be promoted through specific stress management training and through workplace designs that reduce hindrance stressors.